2021
DOI: 10.1093/mmy/myab058
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on distribution and antifungal resistance pattern ofCandidaspecies in the Indian population

Abstract: The emergence of antifungal drug resistance in Candida species has led to increased morbidity and mortality in immunocompromised patients. Understanding species distribution and antifungal drug resistance patterns is an essential step for novel drug development. A systematic review was performed addressing this challenge in India with keywords inclusive of ‘Candida’, ‘Antifungal Drug Resistance’, ‘Candidemia’, ‘Candidiasis’ and ‘India’. A total of 106 studies (January 1978-March 2020) from 20 Indian states wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
1
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 104 publications
3
8
1
2
Order By: Relevance
“…Apart from this, catheterization, mechanical ventilation, elderly patients, empirical antifungal therapy, and surgeries are secondary risk factors [ 21 , 26 , 27 , 29–37 , 94 , 101 ]. The risk factors reported in the present study are comparable to the findings of other studies [ 105 , 61 , 121 , 122 ]. The health care workers need special attention to hand washing or decontamination and provide an aseptic environment to minimize the horizontal transmission of candidiasis in the hospital.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Apart from this, catheterization, mechanical ventilation, elderly patients, empirical antifungal therapy, and surgeries are secondary risk factors [ 21 , 26 , 27 , 29–37 , 94 , 101 ]. The risk factors reported in the present study are comparable to the findings of other studies [ 105 , 61 , 121 , 122 ]. The health care workers need special attention to hand washing or decontamination and provide an aseptic environment to minimize the horizontal transmission of candidiasis in the hospital.…”
Section: Discussionsupporting
confidence: 91%
“…This drift contrasts with many European countries and North America, where the C. glabrata is more prevalent among the non- C. albicans isolates [ 104 ]. However, a similar trend of Candida species prevalence resembling our study was also reported in India, Nigeria, and Cameroon [ 105 ]. Among the infection types, a high proportion of C. albicans was associated with VVC.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, the C. glabrata was detected in 18 cases, the highest among non-C. albicans species. This differs from the studies reported in Cameroon, Nigeria, and India, where C. tropicalis are more prevalent than C. glabrata (Verma et al, 2021). However, a similar drift was observed in North America and many European countries (Song et al, 2020).…”
Section: Discussioncontrasting
confidence: 87%
“…They may be of particular interest in some areas, such as South Asia, where the rate of fluconazole resistance is particularly high due to the high prevalence of C. auris and the increasing rate of fluconazole-resistant C. tropicalis . 9 , 10 , 16 …”
Section: The Place Of Novel Antifungal Agents In the Prevention And T...mentioning
confidence: 99%